2009
DOI: 10.1038/cgt.2009.35
|View full text |Cite
|
Sign up to set email alerts
|

WT1 gene silencing by aerosol delivery of PEI–RNAi complexes inhibits B16-F10 lung metastases growth

Abstract: The Wilms' tumor gene 1 (WT1) is a universal tumor antigen and consequently a good therapeutic target for the development of gene therapy strategies. Earlier, we reported the in vitro efficacy of WT1 RNAi in the inhibition of B16F10 murine melanoma cell line growth. In this study, we used an aerosol system to deliver WT1 RNAi complexes, polyethyleneimine (PEI)-WT1-1 or PEI-WT1-2, to the lungs of mice with B16F10 lung metastasis. This treatment produced a statistically significant (P ¼ 0.020) reduction in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 50 publications
0
57
1
Order By: Relevance
“…It was previously reported that the B16F10 melanoma cell line has high WT1 expression and that downregulation of this protein by RNAi is capable of inhibiting its growth [Zamora-Avila et al (27)]. To determine the LD50s to WT1-1 and WT1-2, we used a MTT assay and western blot analysis to characterize the effect of the downregulation of WT1 expression in the B16F10 cell line.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was previously reported that the B16F10 melanoma cell line has high WT1 expression and that downregulation of this protein by RNAi is capable of inhibiting its growth [Zamora-Avila et al (27)]. To determine the LD50s to WT1-1 and WT1-2, we used a MTT assay and western blot analysis to characterize the effect of the downregulation of WT1 expression in the B16F10 cell line.…”
Section: Resultsmentioning
confidence: 99%
“…B16F10 cells were transfected with WT1-1, WT1-2 and pEGFP-N2 plasmids (Clontech) using 25 kDa of cationic polymer branched polyethylenimine (PEI). The complex PEI: DNA was performed as described by Zamora-Avila et al (27). Following 72 h, a MTT assay was performed.…”
Section: Rnai and Drugs Screening To Median Lethal Dose (Ld50)%mentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary administration of PEI-RNA and WT1 (Wilms' tumor gene) complex was successfully delivered as an aerosol to the lungs of mice bearing B16-F10 melanoma metastases [60]. The PEI-RNA-WT1 complex promoted the apoptosis of B16-F10 cancer…”
Section: Polyethyleneimine (Pei)-drug Conjugatesmentioning
confidence: 99%
“…Indeed, clinical trials using WT1 peptide vaccines have shown effects in reducing adult leukemia cell counts and also promoting shrinkage of solid tumors. 6,9,[11][12][13] Thus, WT1 is a significant target for therapy in both pediatric and adult tumors. However, because WT1 can act as both a tumor suppressor and an oncogene, effective therapies will need to enhance WT1 activity in the former and ablate it in the latter.…”
Section: The Destruction Of Wt1 By Htra2mentioning
confidence: 99%